2019
DOI: 10.3390/ijerph16203862
|View full text |Cite
|
Sign up to set email alerts
|

Engagement of Fathers in Parent Group Interventions for Children with Congenital Zika Syndrome: A Qualitative Study

Abstract: We aimed to explore the engagement of fathers in a community-based group intervention (Juntos) for children with congenital Zika syndrome (CZS) and their caregivers in Brazil. Six Juntos groups were facilitated from August 2017 to May 2018. We conducted a qualitative study to evaluate the feasibility and acceptability of the intervention for fathers of children with CZS. Methods included participant observation, focus group discussions, and semi-structured interviews of fathers with a child enrolled in the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 32 publications
(39 reference statements)
0
36
0
1
Order By: Relevance
“…This is particularly the case for researchers who will be measuring the effect of rehabilitation and support interventions for families. 27 In particular, the importance that parents place on environmental factors for the wellbeing of their children demonstrates the real need to include this environmental context as an aspect to be assessed in the follow-up of children with CZS. 28 29 Our study has demonstrated that the lack of trained professionals to support families is a major issue for parents that needs to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…This is particularly the case for researchers who will be measuring the effect of rehabilitation and support interventions for families. 27 In particular, the importance that parents place on environmental factors for the wellbeing of their children demonstrates the real need to include this environmental context as an aspect to be assessed in the follow-up of children with CZS. 28 29 Our study has demonstrated that the lack of trained professionals to support families is a major issue for parents that needs to be addressed.…”
Section: Discussionmentioning
confidence: 99%
“…New innovations in Juntos, which were not in GTCKP or EIP, include information on the Zika virus, strengthened participatory approaches to engage participants with community inclusion and disability rights, and a concerted effort to improve male engagement, 19 which was successful to a degree (though the female engagement was still much higher). Additional content includes group discussion on gastrostomy (dysphagia was a common problem), creating trousers stuffed with padding to support children in sitting, using an elasticated cloth to rock children who are irritable, and activities to promote understanding of disability rights.…”
Section: Pilotingmentioning
confidence: 99%
“…Our needs analysis in Brazil demonstrated a support programme for families of children with CZS was relevant and needed and a parent group intervention to provide psychosocial support and improve the skills of caregivers to optimally care for their child may fill an important gap in the Zika response 9 . We used evidenced-based approaches to develop the 'Juntos' intervention to address this gap [10][11][12][13] . 'Juntos' (meaning 'together' in Portuguese and Spanish) consists of 10modular weekly group sessions offered over a three-month period, in the community.…”
Section: Introductionmentioning
confidence: 99%
“…A feasibility study was undertaken from August 2017 to June 2018 with six parent groups in two locations of Brazil -Rio de Janeiro and Greater Salvador, Bahia 10 . Satisfaction and acceptability were high and demand was expressed by participants, facilitators, co-ordinators and stakeholders 11,12 . A question remains of the feasibility in other settings.…”
Section: Introductionmentioning
confidence: 99%